Identification of Factors Associated with Nocturnal Enuresis in Children: A Hospital-Based Study (The Planet, 2023)
Background: Bedwetting, also known as nocturnalenuresis, is a common occurrence among children globallyand can lead to social difficulties. It is believed to be causedby a delay in the somatic mechanism responsible formaintaining dryness during sleep. Objective: This presentstudy aimed to identify the associated factors of enuresis inchildren and determine the common methods for itsmanagement. Methodology: This cross-sectional study wasconducted at Mymensingh Medical College Hospital'sDepartment of Pediatrics in collaboration with theMicrobiology and Biochemistry departments over a sixmonth period from protocol approval. Data were collectedby taking a detailed history, thorough physical examination,routine examination, and urine culture. To acquire the rightresult, check list and data coding were examined aftersorting and processing data. Enuresis causes stress and morbidity, hence we investigated itscauses. Using the chi-square test (X2-test), variables were associated. Results: Most patients(43.4%) are 6-8 years old, followed by 32.5% in 8-10 years and 24.1% in 10-12 years. In ourseries, men predominated. Nocturnal enuresis lasted less than 1 year in 74.7% of patients, 2-3years in 16.7%, and 4-5 years in 8.4%. 42.2% of youngsters enurese three times a week, 41.0%more than three times, and 16.9% two times. The majority (66.3%) of children had familyhistory of enuresis: siblings 25.3%, father 24.1%, and mother 16.9%. 8.4% reported lowerstomach pain, 15.7% had burning during micturition. Developmental delay was 7.2%. Treatment improved 78.6% of 28 children. Conclusion: Nocturnal enuresis (NE) is a commonpediatric health problem that can lead to low self-esteem and psychological problems.Awareness, prevention, and effective treatment are important.
Keywords: Enuresis; Nocturnal; Bedwetting